Short Term Outcome of Urethral Meatal Stenosis Surgery in Males - Qazi Adil Inam, Ashfaq Ali, Tasawar Hussain Chatta, Furqan Arshad, Tufail Hussain Tahir, Hasnat Shabbir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: MS is one of the common urological problems that is acquired and is faced by urologists as well as pediatric surgeons. Symptomatic boys are offered meatoplasty or meatotomy as a procedure of daycare under the influence of any anesthesia for the treatment of meatal stenosis. However, there is scarcity of literature on outcome of these surgical procedures in Pakistan. Objective: To determine the short-term Outcome of urethral meatal stenosis surgery in males was the objective of this study. Methodology: this prospective study including 50 male patients with urethral metal stenosis was conducted in department of urology, Aziz Bhatti Shaheed Hospital, Nawaz Sharif Medical College Gujrat, from June 2017 to June 2022. All patients underwent meatotomy. Operative findings and success rate were recorded. Results: Mean age of patients was 8.42±3.91 years. All patients were male. Pre-operatively, 36% patients had Meatal stenosis, 2% Meatal stenosis with incomplete circumcision, 8% Moderate meatal stenosis, 2% Narrowed external urethral meatus, 40% Pinhole meatus, 4% Pinhole sub-coronal meatus, 2% Pinhole external meatus, 4% Severe meatal stenosis and 2% patients had Sub-coronal hypospadiasis Pinhole meatus. The success rate is 100% in our study. Conclusions: Success rate of meatotomy in urethral meatal stenosis is high in male children and younger males. Keywords: meatal stenosis; Outcome; meatotomy